Orthodontic Management of Malocclusion with Anterior and Posterior Crossbite: A case Report - Chaudhary, Nabin Kumar; Chaudhary, Suvin (Medical Journal of Shree Birendra Hospital, 2023)
Crossbite affects the growth and development of teeth and jaws, temporomandibular joint, and masticatory system. This malocclusion should be corrected when first diagnosed. This case report presents the case of skeletal class II malocclusion with unilateral posterior crossbite as well as anterior crossbite, which were managed with activation of transpalatal arch (TPA) and fixed orthodontic appliance. This case is unique as the management of posterior crossbite with TPA is scarce in the literature. The patient was satisfied as both the anterior and posterior crossbite, and competency of the lip were achieved at the end of treatment.